Let's go visit the school - Bernthal, Mark; Full, Dennis (New York Scholastic, 2007)
"Join Barney and Baby Bop as they visit a preschool and learn all about how much fun it is. Baby Bop meets Scamper the guinea pig, listens to stories, paints, and builds a sand castle! What will be her favorite part of the day?"--Cover back
Originally published: Barney & Baby Bop go to school
English Stories
Keywords: Barney (Fictitious character) -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Nursery schools -- Juvenile fiction; Schools -- Juvenile fiction; Dinosaurs -- Fiction; Nursery schools -- Fiction; Schools -- Fiction